واقع العلاقات العامة في مؤسسة الدهن سوق أهراس - مناصرية بوجمعة; ضحاك محمد الشريف; صيد حياة (My University, 2012)
Summary: The public relations function should focus on internal audiences, by preparing weekly or monthly reports explaining the organization's role and achievements in the near and distant future. It should also be directed to external audiences, building a relationship of trust between the organization and its audience through the honesty and objectivity of the information it shares. ---------------------- الملخص: مهمة العلاقات العامة يجب إن تتركز على الجمهور الداخلي من حيث إعداد تقارير أسبوعية أو شهرية تشرح من خلالها دور المؤسسة وانجازاتها في المستقبل القريب والبعيد ، ولتوجه إلى الجمهور الخارجي لبناء علاقة ثقة بين المؤسسة والجمهور من خلال صدق وموضوعية المعلومات التي تشاطرهم بها.
Keywords: واقع العلاقات العامة، مؤسسة الدهن، سوق أهراس